Climate Change Impacts on Surface Runoff and Farmers’ Perceptions of Climate Change: A Case of Mundeni Aru Lower River Basin in Sri Lanka - Rajagopalasingam, V.; Mikunthan, T.; Sivakumar, S.S. (ResearchGate, 2020)
Sri Lanka is one of the Asian countries that is mostly affected by climate change. The prime objectives of this research study were to examine the climate change impacts on surface runoff of Mundeni Aru lower river basin in Sri Lanka and to investigate farmers’ perceptions of climate change. Data which include rainfall, soil data, land use and land cover and antecedent soil moisture condition of the study area were collected from natural resource management center, Department of Agriculture, FAO website and department of meteorology. Further, primary data for perception of climate change was collected through focus group discussions and in depth interviews with key informants of eighty two respondents in lower Mundeni Aru river basins. To analyze the surface runoff, the Soil Conservation Service-Curve Number method has been used. Descriptive statistics were analyzing using SPSS statistical packages for qualitative data and coefficient of variation for seasonal rainfall. NASA Earth Exchange Global Daily Down scaled Projections of 6 General Circulation Models were used for future projections of climate change. This research findings reveals that Mundeni Aru river basin is sensitive to climate change and decreases annual surface runoff by 8%, 10.5% in 2050, 2080 years scenarios respectively but increase annual surface runoff by 2% in 2030 scenario. Moreover, qualitative study finding shows that majority of the respondents agreed that climate change is occurring in the focal area. The calculated coefficient of variation for seasonal rainfall was 0.37 for the last 20 years and compatible with qualitative findings
Keywords: Mundeni Aru; Curve Number; Runoff, River basin